Storage Stability of Additive-free Salacca sp. Fruit Leather - Umi Purwandari; Mojiono Mojiono; Ninik Wulandari K Putri; Miftakhul Efendi; Alfan Wijaya (Indonesian Journal of Agricultural Research, 2018)
We developed additive-free fruit leather made from snake fruit (Salacca sp.), one of the exotic fruits of Madura, Indonesia. Mature snake fruit variety native of Bangkalan Regency was peeled, the seed was discarded, and flesh was blanched for 5 minutes, cooled and then crushed in an electric blender to form a smooth slurry. The slurry was then cooked until thick, spread onto a flat surface, and then dried in an oven at 60°C until dry. Fruit leather with a water content of around 10% was kept in aluminium foil or polypropylene plastic bag at 25 and 35°C for 3 weeks. Every week, fruit leather was examined for tensile strength, water activity, colour (L, a b*values), and titratable acidity. Sensory analysis was performed using ten semi-trained panellists to score hardness, chewiness, sweetness, astringency, aroma, shininess, and cohesiveness. Results indicated that tensile strength apparently increased during storage. Polypropylene bag showed lower water activity and value, but higher titratable acidity of fruit leather. Storage time increased water activity, titratable acidity, but reduced all colour parameters. Higher storage temperature led to higher L and b values. On the contrary, sensory analysis results indicated the limited effect of factors studied. The shininess of fruit leather reduced with the progress of storage, and cohesiveness increased in the first week of storage only, followed by constant reduce towards the storage time. Astringency in snake fruit is a limiting factor. However, snake fruit leather showed moderate level (4.6 out of 9 score) of astringency.